2004
DOI: 10.1042/bj20040145
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of a crystalline (1 3,1 4)-beta-d-glucan by a mutated (1 3,1 4)-beta-d-glucanase from Bacillus

Abstract: Oligo- and poly-saccharides have a large number of important biological functions, and they occur in natural composite materials, such as plant cell walls, where they self-assemble during biosynthesis in a poorly understood manner. They can also be used for the formation of artificial composite materials with industrial applications. Fundamental and applied research in biology and nanobiotechnology would benefit from the possibility of synthesizing tailor-made oligo-/poly-saccharides. In the present paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
(50 reference statements)
0
56
0
Order By: Relevance
“…3, 1!4)-b-d-glucanase from Bacillus licheniformis and a-laminaribiosyl fluoride to produce oligosaccharides (degree of polymerization 6-12). [33] Recently, it was demonstrated that GH10 xylanases can also serve as glycosynthases. Kim et al [18] converted Cellulomonas fimi xylanase into a glycosynthase by replacing its nucleophile Glu235 by Gly.…”
Section: Synthesis Of Xylooligosaccharides In a Conjugated Reactionmentioning
confidence: 99%
“…3, 1!4)-b-d-glucanase from Bacillus licheniformis and a-laminaribiosyl fluoride to produce oligosaccharides (degree of polymerization 6-12). [33] Recently, it was demonstrated that GH10 xylanases can also serve as glycosynthases. Kim et al [18] converted Cellulomonas fimi xylanase into a glycosynthase by replacing its nucleophile Glu235 by Gly.…”
Section: Synthesis Of Xylooligosaccharides In a Conjugated Reactionmentioning
confidence: 99%
“…In both cases these novel catalysts, named glycosynthases , synthesize oligosaccharides with almost quantitative yields. Interestingly, a novel b-glucan containing mixed b-1,3 and b-1,4 bonds was recently obtained by using glucansynthases , indicating that the synthesis of biomaterials can be another useful application of this approach (Faijes et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A 2-D [ 13 C, 1 H] heteronuclear single quantum correlation (HSQC) spectrum (not shown) revealed that the carbon atoms of the biomass components were covalently bonded to protons with 1 H chemical shifts in the range 3.26-5.43 ppm. These chemical shifts and spectra compared well with published 13 C and 1 H chemical shifts and spectra of -glucans (24)(25)(26)(27)(28), which are polymers of glucose. The presence of many 13 C signals near 80 ppm indicated that the -glucans were a mixture of -(1,3) and -(1,4) glucans (24,26,28).…”
Section: Resultsmentioning
confidence: 53%